Existence of solution for a class of nonlocal elliptic problem via sub–supersolution method. (June 2015) - Alves, Claudianor O.; Covei, Dragoş-Pătru
Abstract: We show the existence of solution for some classes of nonlocal problems. Our proof combines the presence of sub and supersolution with the pseudomonotone operators theory.